2015
DOI: 10.1080/08975930.2014.956974
|View full text |Cite
|
Sign up to set email alerts
|

Studying Abroad: Understanding the Relationships Among Beliefs, Perceived Value, and Behavioral Intentions

Abstract: Increased globalization highlights the importance of encouraging university students to participate in an international experience. In this study, the authors investigate how behavioral belief, subjective belief, and control belief influence students' perceived value and intention to study abroad. The authors further examine the moderation effects of generation on the proposed relationships. The results show that behavioral belief, not subjective belief and control belief, is significantly related to perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
1
8
2
Order By: Relevance
“…Each of these is assumed to lead to intention toward the behavior and, in turn, actual behavioral engagement or avoidance. Several studies have found support for attitudes, subjective norms, and perceived behavioral control in predicting study abroad intention and action (Fitzsimmons et al, 2013; Goel et al, 2010; Presley et al, 2010; Schnusenberg & de Jong, 2012; Zhuang et al, 2015).…”
Section: The Choice To Study Abroadmentioning
confidence: 99%
“…Each of these is assumed to lead to intention toward the behavior and, in turn, actual behavioral engagement or avoidance. Several studies have found support for attitudes, subjective norms, and perceived behavioral control in predicting study abroad intention and action (Fitzsimmons et al, 2013; Goel et al, 2010; Presley et al, 2010; Schnusenberg & de Jong, 2012; Zhuang et al, 2015).…”
Section: The Choice To Study Abroadmentioning
confidence: 99%
“…The theory of planned behavior (TPB) of Ajzen (1991), which is widely used in studies on studying abroad behavior (Goel et al, 2010;Petzold & Moog, 2017;Presley et al, 2010;Schnusenberg et al, 2012;Zhuang et al, 2015), is the ground theory in this research. TPB theory indicates that "attitudes", "subjective norms" and "perceived behavioral control" are three important antecedents that predict behavioral intention (Pham et al, 2021).…”
Section: Research Approaches On the Factors Affecting The Intention O...mentioning
confidence: 99%
“…Beliefs refer to ideas that individuals accept as true without verification (Murphy & Mason, 2006). Behavioral beliefs are related to the perceived value of performing an action (Zhuang, King, & Carnes, 2015). In an organizational context, beliefs are defined as conceptions that people possess regarding work, organizations, and society (Heery & Noon, 2001).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%